Nemški Pavliha v primerjavi s svojo predlogo Tyll Eulenspiegels wunderbare und seltsame Historien - Javor Briški, Marija (Vestnik za tuje jezike, 2017)
With sociohistorical background of the target audience in mind, the article compares the Slovene translation Nemški Pavliha with its newly rediscovered original, Tyll Eulenspiegels wunderbare und seltsame Historien, in terms of content, structure, media, and phraseology.
Keywords: Pavliha; Eulenspiegel; frazemi; literarno prevajanje; literary translation; prevod; translation; 19. st.; idioms; evropska književnost; 19th century; Europena literature